FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKTAATAN MASYARAKAT TERHADAP PASAL 57 AYAT 1 PASAL 68 AYAT 1 PASAL 77 AYAT 1 UNDANG-UNDANG NO.22 TAHUN 2009 TENTANG LALU LINTAS DI KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Afriani, Dini; Zahirman, Zahirman; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know factors affecting disobedience of community of Article 57 Paragraph 1 Article 68 Paragraph 1 Article 77 Paragraph 1 Law Number 22 of 2009 on traffic in the Subdistrict Kelayang Indragiri Hulu. The respondents in this study were 100 people by using Sampling Insidental technique. The technique of data collection conducted through Observations, interviews, Questionnaires, and documentation. The research method used is descriptive quantitative analysis research. This method is done with the data processing results of the data presented via the calculation of a percentage of the question form. Based on the results of research conducted on factors affecting disobedience of community of Article 57 Paragraph 1 Article 68 Paragraph 1 Article 77 Paragraph 1 Law Number 22 of 2009 on traffic in the Subdistrict Kelayang Indragiri Hulu, then it can be drawn the conclusion that the overall data regarding the factors affecting disobedience that human factors are a causal factors with percentage of 51,77%. Based on the results of research and analysis of the data, the researchers then give recommendations to the community Subdistrict Kelayang in oerder to have a traffic legal awareness attitude to archieve safe,smooth, olderly, and safe condition on the highway.Key Words: Factors, Disobedience, Traffic, Community